Распространение электромагнитных ТМ волн в нелинейной подложке с линейным поглощением - Г, Очирбат; Д, Улам-Оргих; Д, Гантулга; О, Нямсүрэн (Scientific transaction of the National University of Mongolia. Physics, 2022)
The scheme used in asymptotical methods of Krilov- Bogolubov-Mytropolsky is modified to solve a set of two Maxwell’s equations in propogation problem of stationary optical TM waves in nonlinear substrate with linear absorption. Simplicity of structures of recurrent calculations affords us to easily obtain solution accurate to enough high order of small parameter.